Identifying and explaining the barriers to organic agriculture development from the viewpoint of Jihad agricultural experts in Urmia - Fatemeh Kazemiyeh; Asma Eidi (علوم محیطی)
Introduction: Organic farming is one of the sustainable agricultural strategies that relies on natural methods to control pests and diseases and has been prevented from using artificial pesticides and herbicides, chemical fertilizers, hormones, and antibiotics. Given the importance of food security and the irreparable damage caused by overuse of chemicals in agriculture and human health, the main purpose of this study is to identify and explain the barriers to the development of organic farming. Due to its special geographical location and variety of agricultural products, West Azerbaijan Province has a high capacity in the production of organic products such as grapes, white berries, pomegranates and apples. Although the history of organic farming has long been common in West Azarbaijan Province, unfortunately, this type of agriculture is currently facing many obstacles and problems, so it is important to identify the factors that prevent the use of organic agriculture and should be addressed to solve these problems.Material and methods: The present study was quantitative-qualitative in terms of practical purpose and research paradigm. In the first stage, barriers to the development of organic agriculture were identified by Delphi method. A purposive sampling method was used to collect information. The statistical population of this stage was 25 university professors, experts, and specialists. In the second stage, the data obtained from the agreement of the experts were provided to the experts as a closed questionnaire. The statistical population of the study at this stage included 101 experts from the Agricultural Jihad Organization of Urmia, which due to the limited statistical population was used to collect information with the census method. In order to analyze the data, the exploratory factor analysis technique was used based on the method of analysis to the main components.Results and discussion: The value of KMO for the set of barriers to organic farming development was 0.79. Therefore, the number of samples was suitable for factor analysis. Bartlett's test score was 3072.307, which was significant at the 1% level. Therefore, it can be concluded that the separation of factors was done correctly and the variables of each factor had a high root correlation with each other. According to the research results, the most important barriers to the development of organic agriculture, respectively, included: barriers to information and agricultural knowledge (lack of sufficient knowledge in the production of organic products), motivational and attitude barriers (lack of interest and resistance of farmers in accepting cultivation of organic products), economic barriers (lack of financial support to withstand the damages of the past), technical-managerial and supportive barriers (unfamiliarity with the techniques and methods of cultivation of organic products and lack of a single and specific trustee for organic products), barriers to use (excessive consumption of chemical fertilizers), and extension barriers (farmers' limited participation in extension and educational programs.Conclusion: Agricultural planners should be guided by solutions in the field of facilitating the export of organic agricultural products, supporting farmers in organic farming, and carrying out extension activities to use the existing capacities in the country. Agricultural research must be done on the use of organic and biological fertilizers instead of chemical fertilizers. Special attention must be paid to organic agriculture in developing strategic plans for agricultural research and appropriate and separate pricing systems for organic products. Training and extension courses in organic farming for farmers and encouraging them to participate in these classes are also encouraged.